Pelatihan Model Pembelajaran Reading Concept Map (Remap) dalam Melatih Keterampilan Berpikir Kreatif dan Keterampilan Literasi Sains Peserta didik Di SMP YAPIS Merauke - Irawan, Ferry; Hanip, Rival (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
The development of the 21st century requires students to be skilled in solving problems in a structured manner and in accordance with scientific principles. Creative thinking skills are one of the main components that are the basis for students because creative thinking skills focus on exploring ideas, producing innovative solutions, finding many correct answers to provide innovative solutions that are rarely put forward by others. Creative thinking emphasizes the responses given by students in solving problems using appropriate methods or approaches. The creative thinking process begins with students identifying problems, conducting evaluations, formulating hypotheses and reviewing hypotheses from various perspectives to communicate the results of their thinking. The application of the Integrated PJBL Remap PjBL learning model can accommodate and help students create new ideas (think creatively) from different perspectives. The Remap learning model is a learning model that requires students to carry out reading activities to obtain various types of information, then they pour it into the form of a concept map to see the concepts built by students in a hierarchical and continuous manner.